HUBUNGAN KELEKATAN DENGAN KECERDASAN EMOSI DAN PENYESUAIAN SOSIALPADA ANAK USIA DINI - henni anggraini; sarah emmanuel (Universitas Muhammadiyah Surabaya, 2016)
Attachment is is the tendency and desire of an individual is a child to seek proximity with their guardians (Monk et all, 2004).There are four basic principles of the bond between parent and child is the physical needs of children for food and warmth that filled by their mother, the encouragement of origin which is owned by the child to cling to the mother's chest, the baby needed to touch and clung by a person, and the disappointment of the baby as it is expelled from in the womb (Bowlby, 1969). The quality of a relationship between a children and a parents are an important factor for development of children. The theory of attachment explained that children need attachment with at least one caregiver to develop emotional and social development. This study aims to determine the relationship between attachment of emotional intelligence and social adjustment in early childhood. This study used quantitative methods to the subject 35 students of class B TK muslimat NU 22 aged 5‐7 years. The collecting of data obtained through a scale of attachment between a child and a parents, the scale of emotional intelligence and social adjustment. Furthermore, the data were analyzed by using Product Moment Pearson correlation analysis using SPSS 21.0 for windows. The result showed that there was a positive and significant relationship between attachment with emotional intelligence and social adjustment in early childhood (rxy1 = 0,537; rxy2= 0,513; p = 0,005 < 0,05).